The effect of plant water potential-based deficit irrigation on physiological reproductive responses of grapevines (cv. Shiraz) in different climatic regions. - Visser, John-Murray (Stellenbosch : Stellenbosch University, 2023)
Thesis (MScAgric)--Stellenbosch University, 2023.